2009
DOI: 10.5539/ies.v2n3p190
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Subject-Verb Agreement: From Novice Writers to Expert Writers

Abstract: Students in higher learning institutions need to write lots of reports based on the projects done. Since they are at the tertiary level of education, they are required to use English in their reports. This is to ensure that they are able to function well in English later at the workplace. Writing requires students to apply rules regarding sentence structures, grammar and also its mechanic that refers to punctuation and capitalization. However, many of the students have problems in applying these rules in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…For instance, the present study finds out that the problem of subject-verb agreement remains unaddressed in teaching English through literature. This finding of the present study is also seconded by a case study conducted by Nayan (2009) who has found out that after spending almost 12 years, the EFL learners remain unable to maintain subject-verb agreement in their expressions. In the same way, Shuib (1991) also finds out that the subject-verb agreement is one of the most challenging problems which are faced by the Malaysian EFL learners.…”
Section: Resultssupporting
confidence: 85%
“…For instance, the present study finds out that the problem of subject-verb agreement remains unaddressed in teaching English through literature. This finding of the present study is also seconded by a case study conducted by Nayan (2009) who has found out that after spending almost 12 years, the EFL learners remain unable to maintain subject-verb agreement in their expressions. In the same way, Shuib (1991) also finds out that the subject-verb agreement is one of the most challenging problems which are faced by the Malaysian EFL learners.…”
Section: Resultssupporting
confidence: 85%
“…The flexibility of space and time will permit students to be relaxed yet attentive in their performances and it will also make the process of learning and monitoring easier. (Surina & Kamaruzaman, 2009) indicated that the teachers should promote the use of MALL. So, looking at the context of MALL's importance its implementation is extremely important in this technology world (Buckenmayer, 2011) where different aspects of technology are exploited for benefiting mankind.…”
Section: Resultsmentioning
confidence: 99%
“…(She very pretty) English sentence: She is very pretty. Nayan and Jusoff (2009) focused their study only on the use of subject-verb agreement among ESL students and concluded that the errors of English subjectverb agreement were due to students' lack of comprehension of the rule as their L1 (Malay language) does not posit rules in subject-verb agreement.…”
Section: Samplementioning
confidence: 99%